PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESA WISATA PULESARI DI DUSUN PULESARI DESA WONOKERTO KECAMATAN TURI KABUPATEN SLEMAN - Rizka Ratna Sari Siregar; Siti Hamidah; Budi Widayanto (Agrisociabus, 2022)
Research aims to (1) Assess the Shapes of community participation in development Pulesari Tourism Village (2) Assess the level of community participation in development Pulesari Tourism Village. This research uses a qualitative method with a case of study approach and retrieval of informants use to Purposive which is the managing director of the Pulesari Tourism Village, the community of pulesari and the staff of Pulesari Tourism Village. Data collection tehcniques with observation, interviews and documentation by testing validity of data using triangulation sources. Data analysis technique with collecting data, data reduction, data presentation, and withdrawal of conclusion and verification. The result of this research are (1) The forms of community participation in development Pulesari Tourism Village was provide ideas, assist in infrastructure, mutual coorporation and gived their skills. (2) The level of community participation in development Pulesari Tourism Village was in the citizen power stage (high participation).Keywords: Community Participation, Development Tourism Village. Forms of Participation, Level of Participation